Photon attenuation properties of concrete produced with pumice aggregate and colemanite addition in different rates and the effect of curing age to these properties - Yaltay, N.; Ekinci, C. E.; Cakir, T.; Oto, B. (Pergamon-Elsevier Science Ltd, 2015)
Radiation shielding properties of lightweight concrete produced with pumice aggregate and colemanite addition in different rates and effect of cure ages to the radiation shielding were investigated by using Co-60 (1250 key) radioactive source. Gamma rays were counted by 0.6 cc, Farmer type PTW (TM) Ion chamber. Experimental results were compared with the theoretical values calculated by WinXCom program. Consequently, colemanite addition make enhancement in the radiation shielding of the lightweight concrete, however there is no directly proportional relation between colemanite rate (0.4-2%) and attenuation properties of the lightweight concrete and cure age especially long timed, raises the linear attenuation coefficient and decreases the mean free path values. The theoretical values were obtained as nearby the experimental results, especially in the later cure ages (360 day). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Colemanite; Cure age; Pumice; Radiation shielding; WinXCom